Patient and caregiver characteristics related to completion of advance directives in terminally ill patients. Issue 1 (30th May 2016) - Ho, Grace W.K.; Skaggs, Lauren; Yenokyan, Gayane; Kellogg, Anela; Johnson, Julie A.; Lee, Mei Ching; Heinze, Katherine; Hughes, Mark T.; Sulmasy, Daniel P.; Kub, Joan; Terry, Peter B.; Astrow, Alan B.; et al.
Abstract: Objective: There is a growing body of literature describing the characteristics of patients who plan for the end of life, but little research has examined how caregivers influence patients' advance care planning (ACP). The purpose of this study was to examine how patient and caregiver characteristics are associated with advance directive (AD) completion among patients diagnosed with a terminal illness. We defined AD completion as having completed a living will and/or identified a healthcare power of attorney. Method: A convenience sample of 206 caregiver–patient dyads was included in the study. All patients were diagnosed with an advanced life-limiting illness. Trained research nurses administered surveys to collect information on patient and caregiver demographics (i.e., age, sex, race, education, marital status, and individual annual income) and patients' diagnoses and completion of AD. Multivariate logistic regression was employed to model predictors for patients' AD completion. Results: Over half of our patient sample (59%) completed an AD. Patients who were older, diagnosed with amyotrophic lateral sclerosis, and with a caregiver who was Caucasian or declined to report an income level were more likely to have an AD in place. Significance of results: Our results suggest that both patient and caregiver characteristics may influence patients' decisions to complete an AD at the end of life. When possible, caregivers should be included in advance care planning for patients who are terminally ill.